2020
DOI: 10.1177/2397847320911631
|View full text |Cite
|
Sign up to set email alerts
|

Statistical treatment of cytotoxicity in Ames bacterial reverse mutation assays can provide additional structure–activity relationship information

Abstract: The bacterial reverse mutation assay, that is, the Ames test, measures mutations that reverse the inactivation of a gene involved in the synthesis of either histidine in Salmonella bacteria or tryptophan in Escherichia coli. The classic dose–response curve of an Ames assay plots number of reverse mutations (“revertants”) on the y-axis versus dose of the test chemical on the x-axis. Frequently, the dose–response curve resembles a parabola with a linear initial slope resulting from the accumulation of mutations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Salmonella or Escherichia coli strains may be reversibly gene-mutated by chemicals that inactivate synthesis of histidine or tryptophan respectively. This bacterial mutation assay is DNA damage by base substitution and known as Ames test [36]. In this work, online prediction of Ames test showed that all Abiraterone products except A-T and A-P were genetically safe to the tested bacteria (Table 3.…”
Section: )mentioning
confidence: 74%
“…Salmonella or Escherichia coli strains may be reversibly gene-mutated by chemicals that inactivate synthesis of histidine or tryptophan respectively. This bacterial mutation assay is DNA damage by base substitution and known as Ames test [36]. In this work, online prediction of Ames test showed that all Abiraterone products except A-T and A-P were genetically safe to the tested bacteria (Table 3.…”
Section: )mentioning
confidence: 74%
“…At higher concentrations, the test product led to a complete inactivation of the bacteria. As the complete inactivation can be a result of either antibacterial efficacy of the test product or a mutagenic effect, no clear result can be concluded on the mutagenic potential of the test product in this case [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on several studies, mutagenic substances may be carcinogenic. 33 Mutations are permanent changes in genes that may be responsible for many genetic disorders that result in certain cancers or syndromes. 34 Cancer is a disease characterized by malignant cells/tissues that grow quickly and uncontrollably and spread to other places in the patient's body.…”
Section: Resultsmentioning
confidence: 99%